Coreless, Contactless Power Supply System with DSP Controlled Active Compensation of Parameter Changes - Marcinek, M.; Holub, M. (Elektronika ir Elektrotechnika, 2014)
Contactless power supply systems are of high interest in small power and large power applications. Many high efficiency contactless systems use the resonant operation mode. A parallel compensation system is presented enlarging overall system safety and allowing for resonant system parameter change while maintaining zero current switching (ZCS) operation. Basics of digital control unit construction and operation are presented. Simulation and experimental results are given for control system operation. Systems performance allows for large resonant circuit parameter drift. Modern DSP control unit minimizes the necessary external circuitry and time delays in case of most important operations. DOI: http://dx.doi.org/10.5755/j01.eee.20.10.4989